Question
Suppose \( f(x)=x^{2}-9 x-2 \). Compute the following: A.) \( f(-1)+f(1)=\square \) B.) \( f(-1)-f(1)=\square \) Question Help: Video
Ask by Johnston Maxwell. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
A.) \( f(-1) + f(1) = -2 \)
B.) \( f(-1) - f(1) = 18 \)
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Unlock
Reviewed and approved by the UpStudy tutoring team
Like
Extra Insights
To solve for \( f(-1) \) and \( f(1) \): 1. Calculate \( f(-1) \): \[ f(-1) = (-1)^2 - 9(-1) - 2 = 1 + 9 - 2 = 8 \] 2. Calculate \( f(1) \): \[ f(1) = (1)^2 - 9(1) - 2 = 1 - 9 - 2 = -10 \] Now, we can find \( f(-1) + f(1) \) and \( f(-1) - f(1) \): A.) \( f(-1) + f(1) = 8 + (-10) = -2 \) B.) \( f(-1) - f(1) = 8 - (-10) = 8 + 10 = 18 \) Thus, the answers are: A.) \( f(-1) + f(1) = -2 \) B.) \( f(-1) - f(1) = 18 \)